2012
DOI: 10.1039/c2dt12359b
|View full text |Cite
|
Sign up to set email alerts
|

Site selectivity and reversibility in the reactions of titanium hydrazides with Si–H, Si–X, C–X and H+ reagents: TiNα 1,2-silane addition, Nβ alkylation, Nα protonation and σ-bond metathesis

Abstract: We report a combined experimental and computational comparative study of the reactions of the homologous titanium dialkyl- and diphenylhydrazido and imido compounds Cp*Ti{MeC(N(i)Pr)(2)}(NNR(2)) (R = Me (1) or Ph (2)) and Cp*Ti{MeC(N(i)Pr)(2)}(NTol) (3) with silanes, halosilanes, alkyl halides and [Et(3)NH][BPh(4)]. Compound 1 underwent reversible Si-H 1,2-addition to Ti=N(α) with RSiH(3) (experimental ΔH ca. -17 kcal mol(-1)), and irreversible addition with PhSiH(2)X (X = Cl, Br). DFT found that the reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 103 publications
1
30
0
Order By: Relevance
“…Therefore, the reaction is a hydride-based reduction. [11] As for 3, the 1 H-29 Si HSQC experiment with J = 7 Hz shows coupling of Si with H1M-H3M, whereas that with J = 200 Hz only shows the coupling of Si with H2M and H3M. The molecular structure of 4 is shown in Figure 2.…”
mentioning
confidence: 87%
“…Therefore, the reaction is a hydride-based reduction. [11] As for 3, the 1 H-29 Si HSQC experiment with J = 7 Hz shows coupling of Si with H1M-H3M, whereas that with J = 200 Hz only shows the coupling of Si with H2M and H3M. The molecular structure of 4 is shown in Figure 2.…”
mentioning
confidence: 87%
“…As part of our ongoing interest in titanium imido and hydrazido chemistry we have reported previously in detail on the synthesis, bonding and reactivity of a series of cyclopentadienyl‐amidinate complexes [Cp*Ti{MeC(N i Pr) 2 }(N t Bu)] ( 5 a ), [Cp*Ti{MeC(N i Pr) 2 }(NAr)] ( 5 b , Ar=Tol or Xyl) and [Cp*Ti{MeC(N i Pr) 2 }(NNRR′)] (R=R′=Ph ( 6 a ) or Me ( 7 ); R=Ph, R′=Me ( 6 b )) 3n. p, 8 The reactions of these compounds with CO 2 , CS 2 , isocyanates, many other polar and non‐polar substrates and silanes are well understood, and provide a good basis for further studies of titanium–nitrogen multiple bond chemistry. In this contribution we report the synthesis and bonding of a new titanium alkylidene hydrazido(2−) complex and its reactivity with a range of substrates, a number of which are studied for the first time with the TiNNCR 2 functional group…”
Section: Introductionmentioning
confidence: 99%
“…Fryzuk and co‐workers reported that the dinitrogen complexes [{(P 2 N 2 )Zr} 2 (μ‐η 2 ‐N 2 )] [P 2 N 2 =PhP(CH 2 SiMe 2 NSiMe 2 CH 2 ) 2 PPh)]3e and [{(NPN)Ta} 2 (μ‐η 1 :η 2 ‐N 2 )(μ‐H) 2 ] ( 2 ; NPN=(PhNSiMe 2 CH 2 ) 2 PPh)3f undergo hydrosilylation to yield new NSi bonds and new terminal metal–hydride complexes derived from one SiH unit, respectively. Clot, Mountford, and co‐workers found that the Ti dimethylhydrazido compound [Cp*Ti{MeC(N i Pr) 2 }(NNMe 2 )] undergoes reversible SiH 1,2‐ addition to TiN α with, for example, PhSiH 3 , forming the Ti–hydride–hydrazide complex [Cp*Ti{MeC(N i Pr) 2 }H{N(NMe 2 )SiH 2 Ph}] 3g …”
Section: Introductionmentioning
confidence: 99%